Assessment of Women Role in Agroforestry Practice in Jos North Local Government Area of Plateau State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study was carried out to assess role of women in agroforestry practice in Jos-North Local Government Area of Plateau State using two study area Mazah and Naraguta. Simple random sampling was used to administered 75 copies of questionnaire in each of the two study areas thereby having a total of 150 selected respondents, out of which 139 was retrieved (Mazah; 75 and Naraguta; 64). Data collected were analyzed using simple descriptive statistics. The results from the study  showed that agroforestry practices carried out in both study areas range from Taungya (55.4%), agri-silviculture (16.5%), shifting cultivation (16.5%), silvo-pastoral (7.2%) and horti-silviculture (4.3%). The specific roles played in agroforestry by respondents range from harvesting of tree products (41.7%), tree planting and maintenance (37.4%), seedling production (8.6%) and processing (3.6%) respectively. The study also showed that agroforestry serves as source of income (44.6%), source of food (24.5%), timber production (16.5%) and medicinal purposes (12.9%). The study was able to establish that agroforestry practices have significant improvement on their crop production, and resultant increase in their incomes. It is therefore recommended that women involvement in agroforestry should be encourage in the study areas through advocacy and availability of inputs that will promote their performance for better output.